THE INFLUENCE OF SELF-EFFICACY ON ACADEMIC STRESS OF ISLAMIC RELIGIOUS EDUCATION MASTERS STUDENTS CLASS OF 2024, SULTAN AGUNG ISLAMIC UNIVERSITY, SEMARANG - Irfan, Alif (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of social support on academic stress in Islamic Religious Education (PAI) Masters students of Class of 2024 at Sultan Agung Islamic University Semarang. The method used is a quantitative approach with data collection techniques through closed questionnaires. The sample in this study amounted to 100 respondents who were selected randomly. The results of the partial test analysis (t-test) show that self-efficacy has a significant effect on academic stress, with a significance value of 0.001 (p <0.05) and a calculated t value of 3.300 which is greater than the t table of 1.98472. This indicates a positive influence between self-efficacy and academic stress. In addition, the coefficient of determination (R square) value of 0.316 indicates that 31% of the variation in academic stress can be explained by the self-efficacy variable, while the remaining 69% is influenced by other factors outside the study. The normality test using the Monte Carlo approach produced a significance value (Sig. 2-tailed) of 0.249, which means that the data is normally distributed. Thus, this study confirms the importance of the role of self-efficacy and social support in reducing students' academic stress.